2008
DOI: 10.1038/sj.bjc.6604459
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro sensitivity testing of minimally passaged and uncultured gliomas with TRAIL and/or chemotherapy drugs

Abstract: TRAIL/Apo-2L has shown promise as an anti-glioma drug, based on investigations of TRAIL sensitivity in established glioma cell lines, but it is not known how accurately TRAIL signalling pathways of glioma cells in vivo are reproduced in these cell lines in vitro. To replicate as closely as possible the in vivo behaviour of malignant glioma cells, 17 early passage glioma cell lines and 5 freshly resected gliomas were exposed to TRAIL-based agents and/or chemotherapeutic drugs. Normal human hepatocytes and astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…These rats were euthanized with CO 2 at 1, 3,5,7,9,11,13,15,17, and 18 days postinoculation. BLI was measured prior to euthanization.…”
Section: Correlation Of Intracranial Tumor Volume By Histopathologicamentioning
confidence: 99%
See 2 more Smart Citations
“…These rats were euthanized with CO 2 at 1, 3,5,7,9,11,13,15,17, and 18 days postinoculation. BLI was measured prior to euthanization.…”
Section: Correlation Of Intracranial Tumor Volume By Histopathologicamentioning
confidence: 99%
“…To address the accuracy of quantitative BLI as an indicator of brainstem tumor size, C6-Luc cells were inoculated into ten untreated rats and tumor size assayed by photon emission and histopathological measurement in individual animals at 1, 3,5,7,9,11,13,15,17, and 18 days following inoculation. On each day, one rat was imaged with BLI and then euthanized to calculate histopathological tumor size.…”
Section: Vcr Toxicity In Healthy Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome resistance, both chemotherapeutic and biological agents have been used with success to sensitize tumor cells to TRAIL-mediated apoptosis. 9,10 Sensitization effects are suggested to occur by potentiation of the mitochiondrial apoptotic Previous studies in mesothelioma, prostate and glioma cells have shown that treatment with the protein synthesis inhibitor anisomycin can increase the sensitivity to TRAIL induced apoptosis. [12][13][14] Anisomycin binds the 60S ribosomal subunit and block peptide bond formation and DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…BLI was used to monitor tumor growth and chemotherapeutic efficacy. VIN is effective against human glioma cells in vitro [28,29], and its physical properties make it a potentially good candidate for intratumoral glioma treatment. Unfortunately, its clinical effectiveness has been limited by the BBB, but as this molecule is water-soluble, direct administration to the tumor via i.c.…”
Section: Introductionmentioning
confidence: 99%